Tracking the pattern of accountability in the age of market-based reform - Zainal Abidin, Nor Azizah (2016)
In response to economic pressures and the growing expectation of citizens, the framework of service delivery in the public service sector has changed continually.Market-based reform strategies such as privatisation, corporatisation, joined-up government and public-private partnerships have dominated the current framework of public service delivery around the globe.The adoption of these strategies has changed not only the framework of service delivery but also the notion of accountability.The objective of this paper is to examine the way in which the notion of accountability has developed in public service delivery, focusing on the adoption of policy strategies under the market state model. Studies show that the framework of accountability in the context of public sector reform appears to be complex, especially in the era of market state model. The involvement of the private sector as a public partner in delivering public services has significantly changed the notion of accountability and we argue that to some extent accountability tends to be eclipsed due to the changes in its accountability focus.